2018
DOI: 10.1017/s0967199418000205
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between electroporation and polyfection in pig sperm: efficiency and cell viability implications

Abstract: SummaryThe aim of this study was to optimize protocols for electroporation (EP) and polyfection (PLF) using polyethyleneimine (PEI) for pig sperm transfection and to determine which method was the most efficient. For EP standardization, different voltages, amounts and times of electric pulses were tested using propidium iodide (PI) as reporter. For PLF standardization, different concentrations of fluorescein isothiocyanate (FITC)-labelled PEI (PEI/FITC) were incubated with sperm for different periods of time. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Meanwhile, the protein levels of PDHX transfected with miR-26a mimic and inhibitor after 24 h and 48 h were also significantly changed. It was reported that, under the condition of low current, electrotransfection has no significant impact on viability, plasma membrane, acrosomal and DNA integrity of boar sperm [63]. Furthermore, the ram sperm viability remained about 80% after electrotransfection [56].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the protein levels of PDHX transfected with miR-26a mimic and inhibitor after 24 h and 48 h were also significantly changed. It was reported that, under the condition of low current, electrotransfection has no significant impact on viability, plasma membrane, acrosomal and DNA integrity of boar sperm [63]. Furthermore, the ram sperm viability remained about 80% after electrotransfection [56].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we use flow cytometry to detect exogenous DNA internalized by sperm cells. Silva et al, using fluorescence in situ hybridization (FISH) shows a transfection rate following incubation around to 17% in swine sperm [37]. On the other hand, Canovas et al detect by flow cytometry around to 29% of sperm cells carrying exogenous DNA after incubation in bovine sperm [38].…”
Section: Discussionmentioning
confidence: 99%
“…PEI with molecular weight of 25,000 or 1800 was used for the preparation of complex of AuNPsÀ PEI as described in supporting information, and solution of AuNPsÀ PEI presented claret and no precipitation of large particles (Figure 2A), [16,17] and the final mass ratio of AuNPs to PEI is about 1.75. The colour of the sample presented consistent with AuNPs of diameter 10 nm submitting.…”
Section: A Noninvasive Delivery Of Dna Into Zygotes By Aunpsà Pei Formentioning
confidence: 99%
“…Results showed that positive signal was obtained in 13 samples, accounting for 56.5% of all the tested 23 tail of transplanted offspring (see Table S2 in supporting information). In following picture ( Figure 5A), samples of 15 cubs from two litters (1-15) were tested, and 4 samples (16)(17)(18)(19) from transplanted embryos untreated by APD as the negative control, and GFP plasmid being a positive control. Results suggested a higher proportion of GFP sequence integrated into the chromosome in AuNPs treated embryos.…”
Section: A Noninvasive Delivery Of Dna Into Zygotes By Aunpsà Pei Formentioning
confidence: 99%